Analysis of Unbalanced Magnetic Pull of a Solid Rotor Induction Motor in a Waste Heat Recovery Generator - Jastrzebski Rafal P; Pilat Adam K (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2025)
In active magnetic bearing control systems, the performance of the closed-loop control and the application can be impaired by external disturbances. This article analyzes the unbalanced magnetic pull forces produced by the eccentricity of a high-speed 1MW 3-phase solid rotor induction motor. The effect of unbalanced magnetic pull on a five-degree-of-freedom active magnetic bearing control and the resulting vibrations are studied. Finite-element-method-based modeling of the electrical machine unbalanced magnetic pull and activemagnetic bearing forces is carried out, and the results are used in the harmonic force analysis and modeling of an active magnetic bearing-rotor system. The overall engineering model comprising the rotor dynamics, unbalanced magnetic pull derived by the finite elementmethod, active magnetic bearing forces, and the controller is tested by time-stepping simulations. The simulations and experimental results are reviewed. The severity of the unbalanced magnetic pull and its effects on the robustness of the active magnetic bearing closed-loop system in a hermetic steam turbogenerator applied in marine waste heat recovery systems are evaluated.